The Management Role of the Golkar Party in Aceh Besar District on Member Election 2019 Legislative - Ansari Muhammad; Kasuwi Saiban; Budhy Prianto (Britain International for Academic Research (BIAR-Publisher), 2022)
The management of the Golkar Party in Aceh Besar Regency is committed to carrying out its role since recruitment is carried out in a closed manner as a means of regeneration and openly by providing the widest opportunity for the people to participate in political activities in order to improve the performance of legislative members which are currently considered inadequate. This is due to the low quality of human resources as a result of the weak mechanism for recruiting legislative candidates. The formulation of the problem in this researchwhat is the role of the Golkar Party administrators in Aceh Besar Regency in the 2019 legislative elections andWhat are the factors that hinder and encourage? for the Golkar Party administrators in carrying out their roles. This study uses a qualitative approach to get an overview of the role of the board of directorsGolkar Party in the 2019 legislative elections. The conclusion of the study shows thatthe board plays a role in recruitment through a closed screening of cadres and also openly to the community, then party administrators have a role in determining them to be legislative candidates. Furthermore, there is socialization that is from the party and there is also socialization by the legislative candidates. Constraintfor the Golkar Party administrators in carrying out their rolesconsists of internal constraints including funding and competition between candidates. Meanwhile, external constraints consist of competition between political parties and figures in the eyes of the community. The competition between political parties is common to Golkar, considering that it is a fighting party and even a winning party, but in the context of Aceh, it is a little different because there are local parties that are still the desire of the community. Then to face the competition, the motivating factor for the Golkar Party is to sacrifice some of its cadres and choose other figures who are considered better in the eyes of the community. It was all done to increase the party's electability.